Un siglo de investigación de la religión en el Perú - Marzal, Manuel M. (1996)
This article tries to present, in its two parts, a thematic-bibliographic balance on the religion of Peru in the 20th century and certain questions that its research has raised today. For this I return to previous works (1983, 1989 and 1995), although now insisting more on the questions. I call religion, based on Durkheim (1912) and Geertz (1965), the system of beliefs, rites, feelings, forms of organization and ethical norms about the divine, which generate certain attitudes and states of mind in the individual and serve to give transcendent meaning to life. However, most of the works reviewed here insist more on the objective dimension than on the subjective dimension of religion; In addition, I exclude from this review books of theology and history of the Church and only exceptionally do I refer to articles, with which my bibliographic universe is smaller than that of Rivera (1985).